The role of Xhosa traditional circumcision in constructing masculinity. (September 2017) - Magodyo, Tapiwa; Andipatin, Michelle; Jackson, Kyle
Ulwaluko is a Xhosa word that refers to an initiation ritual. The purpose is to transform boys into men. Circumcision is one of the rituals performed. The ritual aims to instil good moral and social values. Due to socio-cultural shifts, the practice of Ulwaluko has changed and this has culminated in instances of criminal activity, drug abuse, risky sexual behaviours, and inhumane behaviours among some of the initiates. There has been a recent upsurge in research on Ulwaluko in South Africa. While many studies examined Ulwaluko from a constructionist framework, very few have focused on subject positions and how Ulwaluko contributes to the construction of masculinity in Xhosa men. Using social constructionist theory, the study employed a qualitative exploratory design and semi-structured interviews that were analysed using thematic decomposition analysis and positioning theory. Seven participants, from a university in Cape Town, aged from 19 to 32 were recruited using purposive sampling. The results of the study reflect the fluidity of masculinity as reported in literature. First, in some of the participants, Ulwaluko created an idealised masculine identity that was chiefly characterised by upholding ritual teachings and yet the same men were burdened by a prescriptive set of masculine role expectations. Second, through self-reflection and critical engagement, some men contested Ulwaluko resulting in the creation of rival masculinities and thus the study created spaces to rethink masculine identities.